SISTEM PEMBUKTIAN DALAM HUKUM ACARA PIDANA TERHADAP KEDUDUKAN HUKUM HASIL AUDIT BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN - Marlyn Jane Arputila (SOCIETAS, 2014)
The realization of a Free State administration is one of the important demands in this reformation era. It was the underlying spirit of the members of the Assembly at the beginning of the reform ationera , and decide to set provision about Implementation State of Clean and Free Corruption , and nepotism role by MPR No. XI / MPR / 1998.This research is directed to the normative legal research. In order to discuss and review of the System of Evidence in Criminal Proceedings against the legal position of the audit results of Finance and Development Supervisory Agency and to get an overview and detailed explanation of the System of Evidence in Criminal Proceedings against the legal position of the audit results of Finance and Development Supervisory Agency.The Proof of the criminal procedural law has the significant role in the process of criminal law enforcement, because the evidence is based on an alleged act of suspects and defendants. The  tools such as the evidence can be used as the material evidence in order to cause the judge's conviction of the correctness of the existence of a criminal offense has been committed by the defendant. Criminal procedural law governing some evidence , namely Article 184 Criminal Procedure Code , Article 185 Criminal Procedure Code ( witness testimony ) , Article 186 of the Criminal Code ( expert testimony ) , Article 187 of the Criminal Procedure Code ( letter ) , Article 188 of the Criminal Procedure Code ( hint ) , Article 189 Criminal Procedure Code ( Description defendant ) . In the case of evidence of corruption based on the Code of Criminal Procedure and the Law No. 31 1999 about eradication of Corruption and Law No. 20 of 2001 on the Amendment of Act No. 31 of 1999 .The result of Auditor of BPK can be classified to the documentary evidence in the law of evidence by the Criminal Procedure Code.